Changes in eating habits in breast cancer patients - Lunar Karmen Grašič; Kozjek Nada Rotovnik; Kovač Milena Blaž (Sciendo, 2020)
Receiving a cancer diagnosis is an important moment in anyone's life. Consequently, many patients are prepared to change their everyday habits and begin to look for advice from a wide range of sources. Women with breast cancer are particularly motivated and committed to making changes to their lifestyle and diet. The purpose of this study was to elucidate the changes in nutritional and other lifestyle habits following breast cancer diagnosis in Slovenia. A further goal was to estimate the proportion of breast cancer patients using dietary supplements and alternative diets or ascertain their desire to attend a consultation with a dietician.